The Implementation of the Family Hope Program in Banggai Regency - Ade Putra Ode Amane; Syahruddin Hattab; Irwan Waris (Faculty of Law, Universitas Pekalongan, 2023)
The Family Hope Program (Indonesia: Program Keluarga Harapan / PKH) in Banggai Regency, a conditional cash transfer initiative aimed at improving the living standards of poor and vulnerable families in Indonesia, faces both successes and persistent challenges. This study aims to analyze the effectiveness of PKH's implementation, focusing on beneficiary identification, aid disbursement, and coordination among stakeholders. Employing a qualitative research approach, the study collected data through in-depth interviews, participant observation, and document analysis, following the Miles and Huberman (1994) model of data reduction, display, and conclusion verification. The findings reveal that while PKH has significantly enhanced access to education and healthcare, particularly increasing school attendance and reducing dropout rates, it faces ongoing issues such as data inaccuracies and coordination difficulties. These challenges, particularly in reaching marginalized communities in remote areas, underscore the need for improved data management and more tailored community engagement strategies. The study concludes that addressing these challenges is crucial for the program to fully realize its potential in alleviating poverty and promoting social welfare in Banggai Regency.